The effect of an occupational therapy mental health day treatment centre on the use of in-patient services in the Western Cape, South Africa. - Engelbrecht, Riekie (Stellenbosch : Stellenbosch University, 2015)
Thesis (MOccTher)--Stellenbosch University, 2015.